Quantification of enzymatic antioxidants (catalase and peroxidase) and non-enzymatic antioxidants (ascorbic acid and chlorogenic acid) in the tender shoots of seven bamboo species and their products, found in Arunachal Pradesh, India - Ch. Sadananda; L.B. Singha; O.P. Tripathi; S. Dilip; K. Premkumar; P. Lulloo (Advances in Bamboo Science, 2023)
This study was undertaken to understand the anti-oxidative properties of products of both enzymatic and non-enzymatic origin derived from bamboo shoots of seven species, namely Dendrocalamus hamiltonii, Phyllostachys bambusoides, Bambusa tulda, Dendrocalamus giganteus, Bambusa pallida, Bambusa balcooa, and Gigantochola macrostachya, as well as three processed bamboo shoot products, namely Hidung (roasted and partially fermented shoot) Eup (moist fermented shoot), and Ekung (dried fermented shoot). The latter three products are widely consumed by the tribal people of Arunachal Pradesh, India. Catalase enzyme activities (CAT) among the shoots were significantly different (F = 18.574, P < 0.001) with the highest values being in B. balcooa and P. bambusoides (2.7 units/g sample) and the lowest in G. macrostachya (0.9 units/g sample), respectively. Peroxidase GPX activity among the shoots and processed products was also significantly different (F= 17.996, P < 0.001 and F= 8.75, P < 0.05, respectively) with a range of between 125.6 and 239.6 GPX units/g for fresh and 170.7–180.3 GPX units/g for processed products. Ascorbic acid contents in the tender shoots of all the species and processed products ranged from 2.35 to 6.1 mg/100 g for fresh tender shoots and 2.23–5.61 mg/100 g for processed products. Chlorogenic acid (CGA) content was estimated to be 0.22–1.16 mg/100 g for fresh material and 0.24–0.26 mg/100 g for processed products. Fresh tender shoots had higher antioxidative properties of both enzymatic and non-enzymatic origin than fermented and processed forms. Higher antioxidant levels were observed in partially fermented Hidung than in the other two processed forms. Bamboo shoots and their processed forms have an adequate level of antioxidant characteristics, making them a nutritious meal that may be included in a healthy diet plan.